High pressures homogenization (HPH) to microencapsulate L. salivarius spp. salivarius in mandarin juice. Probiotic survival and in vitro digestion. (January 2019) - Calabuig-Jiménez, Laura; Betoret, Ester; Betoret, Noelia; Patrignani, Francesca; Barrera, Cristina; Seguí, Lucía; Lanciotti, Rosalba; Dalla Rosa, Marco
Highlights: HPH at 70 MPa is a suitable technology to microencapsulate L. salivarius spp. s alivarius. Capsules of L. salivarius spp. s alivarius interact with suspended pulp when added to mandarin juice. Encapsulation effect on probiotic survival during in vitro digestion depends on the storage time. After 10 days, the encapsulated probiotic content was higher than that for non-encapsulated one. The encapsulation method efficiency and the stability of the coating could explain the results.